Pork DNA Contamination in Pharmaceutical Products: A Review - Widya Firma, Nonik; Azizah, Zikra; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: A country with a muslim majority population, halal in food product as well as no food product including pharmaceutical product has been main concerned. Several materials which used on pharmaceutical product such as gelatin, collagen and fat content synthesized or extracted from mammalia such as bovine, fish, and also porcine. Product sourced from pork and its derivatives was prohibited for muslim . This review presents about methods to detect pork content in pharmaceutical products and information about pharmaceutical products that are positively contaminated with pork ingredients and their derivatives related to halal status for muslims. Data Sources Study Selection: The method used in this research was study of literature. Literatures used in this paper were based on publication of the last ten years (2010-2020). Data sources of this review article taken from various online journal search sites such as digital library, Google, Google Scholar, PubMed, Science Direct, and E-Resources. Conclusion: Conclusion: A result of this review were found 36 capsule samples, 7 gelatin of soft candy gelatin, 4 cosmetic product, amniotic fluid, placenta, oleic acid, stearate acid/stearic alcohol, lanolin alcohol and propylene glycol are positive contain pork DNA. The analytical method used to detect the content of pork and its derivatives in pharmaceutical products such as PCR, HPLC, Nano UPLCESI-Q-TOFMS, FTIR, Liquid Chromatography–Tandem Mass Spectroscopy, Liquid Scintillation Counting, PEME, ELISA, and SDS-PAGE Both Conventional and Combined.